(untitled) (Mediscope, 2018)
Septic arthritis is an uncommon form of arthritis in children. A five years old boy presented with pain and swelling of both knee joints for 7 days. His joints swellings were disproportionate to pain. He had no history of trauma to the joints. On examination, there was soft tissue swelling of both knee joints. Investigation showed features of acute inflammation. Plain radiograph showed soft tissue swelling. Ultrasonography showed fluid accumulation in joints space. After 7 days of antistaphylococcal therapy, the child improved significantly. Physicians treating the children need to be aware of taking proper history and doing physical examination and checking laboratory findings of the children with septic arthritis for appropriate case management. Mediscope Vol. 6, No. 1: Jan 2019, Page 41-43